The Effect of Telehealth Services on Provider Productivity. Issue 5 (17th May 2021) - Stefos, Theodore; Carey, Kathleen; Shen, Mei-Ling; Poe, Stacy; Oh, Dennis H.; Moran, Eileen
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Telehealth services historically have played a small role in the provision of health care in the United States. However during the coronavirus disease 2019 (COVID-19) pandemic, public and private insurers rapidly expanded access to telehealth in order to reduce exposure and avoid transmission. It is unknown whether telehealth will become a more regular substitute for in-person care beyond the pandemic. Objective: Our objective was to provide evidence on the value of telehealth by comparing the productivity of physicians and other specialized clinicians who provide telehealth with the productivity of those who do not. Research Design: We conducted a retrospective data analysis of 17, 705 unique providers in the areas of internal medicine, cardiology, dermatology, psychiatry, psychology, and optometry practicing in the US veterans affairs health care system during the period 2015 to 2018. For each year, we measured individual providers productivity by the total number of relative value units (RVUs) per full-time equivalent (FTE). We estimated the impact of providing telehealth on RVUs/FTE using fixed effects regression models estimated on a panel dataset of 58, 873 provider-year observations and controlling for provider and patient characteristics. Results: Overall provider productivity increased in veterans affairs over the period, particularly in cardiology and dermatology. Providers of telehealth had above average productivity by 124 RVUs/FTE, or ∼4% of average total provider productivity. For the highest quartile of telehealth providers, average productivity was 188 RVUs/FTE higher than productivity of other providers. Conclusion: Strategies that encourage long-term integration of telehealth into provider practices may contribute to overall health care value.